El conocimiento: un intangible generador de innovaciones (2012)
Definitely in the first decade of XXI century there have been great and deep changes in markets and with them come the need to recombine the various resources of organizations seeking to create high value in order to promote sustainable competitive advantages that enable them to join the knowledge society, as expressed by the studies of Castells (1996) and OECD (2001). These new requirements make more complex the management of organizations and lead us to analyze them from the standpoint of intangibles. Innovation is the key element that guarantees sustainability and permanence in international markets, becoming it the business engine that is fueled by intellectual capital based on knowledge.